Gamma interferon-induced T-cell loss in virulent Mycobacterium avium infection - Florido, M (2005)
Infection by virulent Mycobacterium avium caused progressive severe lymphopenia in C57BL/6 mice due to increased apoptosis rates. T-cell depletion did not occur in gamma interferon (IFN-gamma)-deficient mice which showed increased T-cell numbers and proliferation; in contrast, deficiency in nitric oxide synthase 2 did not prevent T-cell loss. Although T-cell loss was IFN-gamma dependent, expression of the IFN-gamma receptor on T cells was not required for depletion. Similarly, while T-cell loss was optimal if the T cells expressed IFN-gamma, CD8(+) T-cell depletion could occur in the absence of T-cell-derived IFN-gamma. Depletion did not require that the T cells be specific for mycobacterial antigen and was not affected by deficiencies in the tumor necrosis factor receptors p55 or p75, the Fas receptor (CD95), or the respiratory burst enzymes or by forced expression of bcl-2 in hematopoietic cells.